Corporate romanticism : liberalism, justice, and the novel - Stout, Daniel (Lit z., 2017)
Innocence you don't have to earn, virtue that you cannot deserve, guilt that never ends, action that never stops, character without innerness, many persons speaking through a single human, a single creature who is also a species, a man who is not himself because he is his double, a man who is neither himself nor his double. These confusions of personhood and action are not exceptions to the law of liberal individualism; they are the confusions that are its only history." 'Corporate Romanticism' offers an alternative history of the connections between modernity, individualism, and the novel. In early nineteenth-century England, two developments - the rise of corporate persons and the expanded scale of industrial action - undermined the basic assumption underpinning both liberalism and the law: that individual human persons can be meaningfully correlated with specific actions and particular effects. Reading a set of important Romantic novels - 'Caleb Williams', 'Mansfield Park', 'The Private Memoirs and Confessions of Justified Sinner', 'Frankenstein', and 'A Tale of Two Cities' - alongside a wide-ranging set of debates in nineteenth-century law and Romantic politics and aesthetics, Daniel Stout argues that the novel, a literary form long understood as a reflection of individualism's ideological ascent, in fact registered the fragile fictionality of accountable individuals in a period defined by corporate actors and expansively entangled fields of action. Examining how liberalism, the law, and the novel all wrestled with the moral implications of a highly collectivized and densely packed modernity, ' Corporate Romanticism' reconfigures our sense of the nineteenth century and its novels